A Case of Pseudohypoparathyroidism Misdiagnosed as Idiopathic Epilepsy for 5 Years: Clinical Analysis and Follow-up Outcomes - Li-Zhen Dai; Chenshi Lin; Rui Lei; Yan Zhang; Hong Ma (Journal of International Medical Research, 2023)
We report a 15-year-old Chinese girl who presented with intermittent seizure episodes and had been misdiagnosed as having idiopathic epilepsy 5 years previously. Laboratory testing revealed hypocalcemia, hyperphosphatemia, and a high parathyroid hormone (PTH) concentration. She was subsequently shown to have pseudohypoparathyroidism type Ib (PHPIb) based on the results of methylation analysis of the GNAS gene, which showed a loss of methylation of the differentially methylated regions (DMR) of GNAS-AS1 , GNAS-XL , and GNAS-A/B ; and a gain of methylation of the DMR of the GNAS-NESP55 region. We adjusted the patient’s medication by prescribing calcium and calcitriol supplements, and gradually reduced the doses of antiepileptic drugs, until they had been completely discontinued. As a result, the patient did not experience any further seizures or epileptiform symptoms; and had normal plasma calcium, phosphorus, and 25-hydroxyvitamin D concentrations and 24-hour urinary calcium excretion. In addition, her PTH concentration gradually normalized over 12 months, and no urinary stones were found on ultrasonographic examination. In conclusion, the clinical presentation of PHP is complex, and the condition is often misdiagnosed. The diagnosis and follow-up of the present patient have provide valuable insights that should contribute to informed clinical decision-making and the implementation of appropriate treatment strategies.